Traumatic Brain Injuries in the Ancient Egypt: Insights from the Edwin Smith Papyrus - Kamp, M. A.; Tahsim-Oglou, Y.; Steiger, H.-J.; Hänggi, D. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background Traumatic brain injury (TBI) is probably as old as human beings. The Edwin Smith Papyrus is the first treatise describing the treatment of patients with TBI and allows insights into the medical examination and treatment of head-injured patients in ancient Egypt.Method Clinical, diagnostic, and therapeutic principles in the treatment of TBI in ancient Egypt were analyzed.Results Methodically, cases and the presentation of each case are neatly classified within the papyrus. The papyrus contains the first description of the brain, pulsations, contusions as the result of TBI, the dura, and cerebrospinal fluid, revealing a more or less sophisticated knowledge of cerebral anatomy. Furthermore, ancient physicians examined wounds, fractures, signs of basal skull fractures, and associated neurological or infectious symptoms, and classified the injury pattern according to their prognosis. Therapeutic options at this time seemed to have been limited.Conclusions The Edwin Smith Papyrus reveals asthonishing observation skill when considering the methods and limits of acient times. These physicians were able to recognize many symptoms of TBI and assign them a prognostic value.
Keywords: Edwin Smith Papyrus; Ancient Egypt; traumatic brain injury